A CONSTRUÇÃO DO CONHECIMENTO FILOSÓFICO: um estudo da proposta de Matthew Lipman nos Anos Iniciais do Ensino Fundamental na Escola Unidade de Educação Básica Monsenhor Frederico Chaves em São Luís - MA - MATOS, Otainan da Silva (2020)
This investigation, transformed into a dissertation, aims to investigate how the Philosophy for Children program can contribute to Basic Education. Therefore, we aim to present the importance of its implementation in early childhood education institutions. Thus, this study talks about the application of the program created by Matthew Lipman, in the Monsenhor Frederico Chaves Basic Education School, to students of the 4th (fourth) year of the Initial Years. In order to achieve our purpose, we present theoretical and methodological discussions to assist in the construction and analysis of the results obtained in the field research, as well as the following question: the Philosophy for Children in public schools in Brazil, has some positive effect on the education of children. small children? Therefore, we resort to studies by authors such as Ariès (1978), Kuhlmann Jr. (1998), Plato (2010), Rousseau (2004), Silveira (2003), Brocanelli (2010), Sharp (1995), Passos, Kastrup and Escóssia (2015), among others. Philosophy for Children, which is the main theme of our work, has the prerogative of dialogue through the Research Community. With this proposal, the development of skills such as critical thinking, communication, cooperation and creativity is encouraged in children. In addition, we emphasize that the Research Community promotes higher order thinking, which in Lipman's conception is understood as thinking systematically. In this way, we seek to analyze how the application of this program helps in the development of children, in order to build a new teaching-learning perspective. In the methodological path, we used several steps, among them the method of cartographic procedure, which aims to go into the field to remove the theoretical part of the experience. Our data collection took place through photographic records, semi-structured interviews and questionnaires. Finally, we emphasize that this study demonstrates that this pedagogical proposal can be inserted in the school environment and in the curriculum as an integral part of Basic Education.